From the Cabinet of Curiosities: The misdirection of research and policy debates on small firm growth. (February 2021) - Hart, Mark; Prashar, Neha; Ri, Anastasia
We would like to thank Professor Mark Hart, Dr Neha Prashar and Dr Anastasia Ri for compiling our Annual Review Article of 2020 which is dedicated to the memory of Michael Anyadike-Danes. Analyses of growth and scalability are of perennial interest given the centrality of this issue and the diverse range of debate it generates; it is clearly of even greater importance during the current pandemic given the disruption to markets and related economic volatility. This review papers offers a refreshing critique of axioms regarding scalability which have been latched onto by policy makers but are not supported by longitudinal evidence and instead, considers alternative pathways for future research. I would like to extend my thanks to the authors and to the referee who commented upon an earlier version of this article, for their valuable contribution to the ISBJ. Understanding business growth, and particularly the growth of small firms, has been the subject of academic enquiry for over 40 years. Yet, it still creates debate and controversy as academics and policy makers wrestle with a rich, complex evidence base. From a policy perspective, 'scaling' is an important dynamic to nurture in the UK economy, but we argue that current discussions about 'scale-ups' are profoundly unhelpful from a policy perspective and has misdirected research effort and public policy resources. We step away from growth rates as the central concern – the preoccupation of the Organisation for Economic Co-Operation and Development (OECD) High-Growth Firm metric – towards 'growth trajectories' which better captures the interplay between growth and survival. It provides a different approach to measuring the contribution of rapidly growing firms to job creation and economic growth.